Determination of F, Na, Mg, Al and P in Indian tea powders by a proton induced γ-ray emission technique. Issue 39 (15th September 2016) - Sunitha, Y.; Sarkar, A.; Kumar, Sanjiv
Abstract : The high sensitivity of proton induced γ-ray emission technique to light elements is exploited to determine F, Na, Mg, Al and P in several Indian tea powders. Abstract : The high sensitivity of proton induced γ-ray emission technique to light elements is exploited to determine F, Na, Mg, Al and P in several Indian tea powders. Measurements are performed on black as well as green tea powders before ( i.e. made tea) and after their infusion (brewing) in hot aqueous medium. Quantification against a Standard Reference Material (SRM) 1571 (orchard leaves) reveals that made tea, in general, contains these elements in a concentration range of a few tens to several hundred mg kg −1 . Although made black or green tea does not have any characteristic elemental profile, green tea, in general, contains Al at elevated levels. The elements are leached from made tea into aqueous medium (liquor) on infusion, as ascertained by analyzing the infused tea powders. The extent of leaching is highest for F and least for Al. These measurements can be used to estimate the concentrations of the elements in liquors. Statistical analysis of the results on solid samples shows that the standard deviation of the measurements is about 4%, while their combined standard uncertainty is 5–20%. The uncertainty in elemental concentrations of SRM is the main contributor to the combined standard uncertainty of the measurements.